Fluoroscopy-guided bone marrow aspiration and biopsy: technical note - Anderanik Tomasian; Jeremiah Long; Jack W. Jennings (Diagnostic and Interventional Radiology, 2021)

(untitled)
Bone marrow aspiration and biopsy is a valuable procedure commonly utilized for evaluation of hematologic abnormalities, nonhematologic malignancies, metabolic abnormalities, tumor treatment response, and suspected infection in patients with fever of unknown origin. Imaging guidance with computed tomography (CT) is commonly utilized to improve safety and effectiveness of the procedure. Considering progressively increasing volume of complex CT-guided procedures as well as diagnostic CT imaging in most practices potentially resulting in limited availability of CT, a technique for fluoroscopy-guided bone marrow aspiration and biopsy is described with focus on advantages, which could be beneficial to most busy practices in modern era radiology.